The Influence Of Independence, Organizational Commitment, And Organizational Culture On Auditor Performance - Zuraidah, Ida; Ladewi, Yuhanis; Putri, Nensi Anisa (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2022)
This study aims to determine and analyze the effect of Independence, Organizational Commitment, and Organizational Culture on Auditor Performance. The type of research used in this research is descriptive and associative research. The location of the research was carried out at the Sumsel Babel Bank. The population in this study were 76 auditors at Bank Sumsel Babel 1, 28 branch offices. The sample used in this study is a saturated sample and the number of samples obtained is 40 auditors. The data used is primary data. The data collection method in this study was a questionnaire. The data testing method used in this research is validity test and reliability test. The analytical technique used in this study is descriptive statistical analysis and inferential statistical analysis, inferential statistical analysis in this study is the classical assumption test (data normality, multicollinearity, heteroscedasticity), multiple linear analysis, coefficient of determination and hypothesis design (t test). The data analysis technique in this study used statistical program for social science (SPSS) version 25. The results showed that the data test showed that the results of the data tested in the form of a questionnaire were all valid and reliable. The analysis technique produced is descriptive statistics per variable which shows a very high dominant value, while the statistics per indicator shows that the dominant value is very high and inferential statistics, namely the classical assumption test, shows that the normality test is normally distributed, does not occur multicollinearity and does not occur heteroscedasticity, while the analysis multiple linear shows that the variables of independence, organizational commitment and organizational culture are considered constant, the auditor's performance will increase. The results of this study can be concluded that independence has an effect on auditor performance, organizational culture has an effect on auditor performance, while organizational commitment has no effect on auditor performance.